Academic Performance as A Function of Psychological Profile and Personality Type - Sofia Shehzad, Zainab Waheed, Hamid Hussain, Samir Khan Kabir, Waleed Ahmad, Muhammad Alamzaib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to evaluate the association and psychological profile, including depression, anxiety, stress, and personality type (Type A and Type B), with the academic performance of the medical students. Methodology: It was a cross-sectional study conducted at different medical colleges in Peshawar. The data was collected from the final year students of MBBS. A total of 325 students participated in the study. Informed consent was taken from the participants. The academic performance (Success and failure) was documented through the annual result sheets of the students. Jenkin’s Personality Survey Questionnaire evaluated personality types, and Depression Anxiety Stress Scale-21 (DASS-21) was used to assess stress, anxiety, and depression. The data was entered and analyzed on SPSS 26. Results: Out of 325 students, 199 were male, and 126 were female. Type A personality students (88.8%) had a high success percentage of academic performance as compared to Type B personality (70.7%). There was an association between Depression, Anxiety, and stress with students’ academic performance. The medical students with low intensity of depression (84.4%), anxiety (84.4%), and stress (83.8%) had more success in academic performance. Conclusion: There is an association between the personality types (Type A and Type B) and psychological profile with the academic performance of the medical students.